LO33: External cold and vibration for pain management of children undergoing needle-related procedures in the emergency department: a randomized controlled non-inferiority trial. (May 2019) - Ballard, A.; Khadra, C.; Adler, S.; Parent, E.; Trottier, E. D.; Bailey, B.; Poonai, N.; Le May, S.
Abstract : Introduction : Needle-related procedures are considered the most important source of pain and distress in children in hospital settings. Time constraints, heavy workload, busy and noisy environment represent barriers to the use of available interventions for pain management during needle-related procedures. Therefore, the use of a rapid, easy-to-use intervention could improve procedural pain management practices. The objective was to determine if a device combining cold and vibration (Buzzy) is non-inferior (no worse) to a topical anesthetic (Maxilene) for pain management in children undergoing needle-related procedures in the Emergency Department (ED).Methods : This study was a randomized, controlled, non-inferiority trial. We enrolled children aged between 4-17 years presenting to the ED and requiring a needle-related procedure. Participants were randomly assigned to the Buzzy or Maxilene group. The primary outcome was the mean difference in pain intensity during the procedure, as measured with the CAS (0-10). Secondary outcomes were procedural distress, success of the procedure at first-attempt and satisfaction of parents.Results : A total of 352 participants were enrolled and 346 were randomized (Buzzy = 172; Maxilene = 174). Mean difference in procedural pain scores between groups was 0.64 (95%CI -0.1 to 1.3), showing that the Buzzy device was not non-inferior to Maxilene according to a non-inferiority margin of 0.70. No significant differences were observed for procedural distress (p = .370) and success of the procedure at first attempt (p = .602). Parents of both groups were very satisfied with both interventions (Buzzy = 7.8 ±2.66; Maxilene = 8.1 ±2.4), but there was no significant difference between groups (p = .236).Conclusion : Non-inferiority of the Buzzy device over a topical anesthetic was not demonstrated for pain management of children during a needle-related procedure in the ED. However, considering that topical anesthetics are underused in the ED setting and require time, the Buzzy device seems to be a promising alternative as it is a rapid, low-cost, easy-to-use and reusable intervention.